Experimental study of different structural parameters on gas lubricated spiral groove thrust bearing for cryogenic turbo expander. Issue 1 (1st May 2022) - Zhang, X H; Li, K R; Yan, H; Zheng, L W; Ke, C L; Dong, B; Peng, N; Liu, L Q; Gong, L H
Abstract: With the development of high speed and miniaturization of turbo expander, the gas-lubricated spiral groove dynamic pressure gas bearing plays an important role. An experimental study on the gas-lubricated spiral groove gas thrust bearing is carried out to research the relationship between the bearing loading capacity and the structural parameters such as the spiral angle, the groove length ratio, the groove width ratio and the rotating speed. The contrast experiment of spiral groove structure on thrust disc and bearing end face was also carried out. The experimental results show that the optimum spiral angle is 20°, the optimum groove length ratio is 0.61∼0.68, the optimum groove width ratio is 0.5∼0.55, and the new structure of the spiral groove on the thrust disc will increase the bearing loading capacity by 7.6% than the traditional structure.